Trigger‐dependent differences determine therapeutic outcome in murine primary hemophagocytic lymphohistiocytosis. Issue 11 (2nd June 2020) - Gather, Ruth; Aichele, Peter; Goos, Nadja; Rohr, Jan; Pircher, Hanspeter; Kögl, Tamara; Zeiser, Robert; Hengel, Hartmut; Schmitt‐Gräff, Annette; Weaver, Casey; Ehl, Stephan
Abstract: Familial hemophagocytic lymphohistiocytosis (FHL) is a hyperinflammatory syndrome affecting patients with genetic cytotoxicity defects. Perforin‐deficient (PKO) mice recapitulate the full clinical picture of FHL after infection with lymphocytic choriomeningitis virus (LCMV). Hyperactivated CD8 + T cells and IFN‐γ have been identified as the key drivers of FHL and represent targets for therapeutic interventions. However, the response of patients is variable. This could be due to trigger‐dependent differences in pathogenesis, which is difficult to address in FHL patients, since the trigger frequently escapes detection. We established an alternative FHL model using intravenous infection of PKO mice with murine CMV (MCMV)Smith . PKO mice developed acute FHL after both infections and fulfilled HLH diagnostic criteria accompanied by excessive IFN‐γ production by disease‐inducing T cells, that enrich in the BM. However, direct comparison of the two infection models disclosed trigger‐dependence of FHL progression and revealed a higher contribution of CD4 T cells and NK cells to IFN‐γ production after MCMV infection. Importantly, therapeutic intervention by IFN‐γ neutralization or CD8 + T‐cell depletion had less benefit in MCMV‐triggered FHL compared to LCMV‐triggered FHL, likely due to MCMV‐induced cytopathology. Thus, the context of the specific triggering viral infection can impact the success of targeted immunotherapeutic HLH control. Abstract : Similar to humans, mice with genetic cytotoxicity defects develop life‐threatening hemophagocytic lymphohistiocytosis (HLH) after exposure to otherwise tolerated viral infections. We show that HLH immunopathogenesis differs depending on the viral trigger, explaining variable effects of therapeutic blockade of CD8 T cells or IFN‐γ in this disease.